Description of two new deep-water species of the genus Brookula Iredale, 1912(Mollusca, Gastropoda, Trochoidea), with a revision of the genus for the Subantarcticand Arctic Sector of the Atlantic Ocean - Schwabe, Enrico; Engl, Winfried (Zootaxa, 2008)
Among benthic mollusc samples from the deep Southern Atlantic Ocean collected during various expeditions of the German Research Vessel Polarstern were several representatives of the genus Brookula, of which four new deep water records are presented herein. Two of the species, B. bohni sp. nov. and B. charleenae sp. nov. are described and differences to congeners are given. For Brookula argentina (Zelaya, Absalão & Pimenta, 2006) and B. exquisita Clarke, 1961 range extensions are provided. The problematic use of the genus Benthobrookula instead of the genus Brookula is discussed and the use of the genus name Benthobrookula is discouraged until more detailed data on morphology and anatomy are available. For the first time the soft part gross morphology of Brookula pfefferi Powell, 1951 has been investigated and illustrated. Brookula decussata (Pelseneer, 1903) has to be regarded as a potential senior synonym of B. pfefferi. Examination of the type material has shown that B. antarctica Dell, 1990 does not differ from B. strebeli Powell, 1951 and the former becomes a junior synonym of B. strebeli. Morphometric data for all Brookula species from the Subantarctic and Antarctic waters of the Southern Atlantic Ocean are also provided, allowing a total of nine species to be included in this sector.